Dietary energy intake during lactation and following weaning; effects on sow and litter performance - Dulohery, S.A.; Nelssen, Jim L.; Davis, Duane L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The effect of energy intake during a 21-day lactation and from weaning to estrus on sow and litter performance was studied. Lactation treatments consisted of two energy intakes, either 8 (Low Energy; LE) or 16 (High Energy, HE) Meal of metabolized energy (ME) per sow per day. Lactation diets were equivalent to daily feed intakes of 6 or 12 lb, respectively, of a grain-soybean meal diet. Energy intake from weaning to first estrus was either 5.5 (LE) or 11 (HE) Meal of ME per sow per day, formulated to approximate feeding of 4 or 8 lb of a grain-soybean meal diet daily. Any sow in estrus by 30 days postweaning was artificially inseminated or hand-mated and fed 4 lb daily of a 14% grain-soybean meal diet during gestation. Sows remained on the same lactation-post weaning energy intakes during two parities. First and second parity sows fed 8 Meal/day during lactation lost more (P<.05) weight and backfat during lactation compared to sows fed 16 Mcal of ME/day. Likewise, litters nursing sows fed LE weighed less at weaning. Regardless of lactation treatments, first-parity sows fed 11 Mcal/day from weaning to first estrus gained more backfat (P<.05) during the first 14 days postweaning and more weight (P<.01) during the initial 28 days postweaning compared to those fed 5.5 Meal of ME/day. Slightly fewer first-parity sows fed LE during lactation were in estrus by 7 days postweaning compared to those fed HE. Increasing energy intake from weaning to first estrus had no effect on percentage of sows exhibiting estrus by 14 days postweaning. These results indicate that increasing the energy intake of first-litter sows during lactation or from weaning to estrus will minimize weight and backfat loss during the feeding period but will not substantially reduce the number of days from weaning to estrus in the first two parities.
Keywords: Swine; Dietary intake; Lactation; Weaning; Sows; Litter Performance